PERANCANGAN SISTEM DAN PENERAPAN METODE MONTE CARLO UNTUK MEMPREDIKSI PERMINTAAN(Studi Kasus: Toko Keluarga) - Nurul Aini (2022)
In the marketing industry, especially staple food, the supply of goods is an important thing that must be done in meeting consumer needs. To meet consumer needs, it is necessary to prepare the right amount of inventory. Inventory items that have excess capacity, can cause several problems. As experienced by Toko SEMBAKO Keluarga, Toko Keluarga often experiences overstock or excess stock which causes problems with capital costs, and utilization of inventory space. These problems can affect the profits obtained by Toko Keluarga, so it takes a prediction on the demand for goods that will occur in the future. Prediction of demand for goods can be done using the Monte Carlo Simulation process. The simulation process is carried out by calculating from the historical transaction data of Toko Keluarga for 12 months (November 2020 - October 2021). The prediction results made using the Monte Carlo Simulation method, yielded an accuracy value of 91%, so that the prediction results were included in the 'Very Good' prediction category, and could be used as a decision-making tool in the process of supplying inventory. Keywords : Overstock, Prediction, Statistics and Probability, Monte Carlo Simulation.